THE EFFECTS OF COOPERATIVE LEARNING STRATEGIES AND ACADEMIC ABILITY TO BIOLOGY LEARNING ACHIEVEMENT - Noviawan, Dwi; Karwono, Karwono; Santoso, Handoko (Lembaga Penelitian UM Metro, 2019)
The research was conducted at SMA Negeri 5 Metro on June 14 until September 30, 2017. Variables of research X1 (STAD and TGT), X2 (Upper and Lower Academic Abilities), Y (Biological Cognitive Learning Outcomes) Experimental Design of Factorial 2 x 2. Sample 56, STAD 28 students, TGT 28 students, was classified based on upper and lower academic ability. Sapling technique stratified random sampling. Documentation and test data collection model. Technique of data analysis of 2 path Anova as further test, previously conducted independent t test and paired t test.Result of a nalysis of research data concluded there is no difference between mean of cognitive biology learning result in group of STAD and TGT value of Sig (2-tailed) equal to 0,689 > 0,05. There is no difference between the mean of biological cognitive learning outcomes in groups of learners capable of upper and lower Sig (2- tailed) values of 0.891 > 0.05. There is no difference in the results of cognitive biology study using STAD and TGT model on students who have high academic ability, Sig 0.854 (p > 0,05).